Emotional labor in sport coaching: a situational approach in the context of elite French handball - Petiot, O.; Fontaine, T.; Dugény, S.; Visioli, J.; Kermarrec, G. (International Journal of Sport and Exercise Psychology, 2025)
Elite sport coaching requires a high level of demanding emotional labor. The aim of this article was to analyze the emotional labor of handball coaches during high-stake elite matches. A situational approach was adopted, in which emotional labor is composed of three interdependent elements: emotional regulation (composed of various enacted forms), emotional experience and emotional inducers. Ten coaches from France`s first and second handball divisions were filmed during fifteen matches and invited to take part in self-confrontation interviews immediately after each match. During these interviews, they were asked to explain how they had regulated their emotional experience throughout the match. Analyzing the coaches` retrospective verbalizations using NVivo Software highlighted 121 moments of emotional labor with four enacted forms of emotional regulation: (1) "Sincerely expressing emotions" (n = 63; 52.1%); (2) "Masking emotions" (n = 30; 24.8%); (3) "Relativizing emotions" (n = 17; 14%); and (4) "Amplifying emotions" (n = 11; 9.1%). Negative emotions accounted for three quarters of these moments of emotional labor (75.2%) and three categories of inducers were highlighted (i.e., "Inappropriate behavior from the players", "Disagreement with a referee`s decision", and "Success of the players"). Statistical analyses showed significant associations between emotional regulation and emotional experience, and between emotional regulation and emotional inducers. Emotional labor therefore appears to be an integral part of coaches` activity during elite matches. The various enacted forms of emotional regulation emerge depending on the emotions experienced and the perceived inducers, thus emphasising the emotional flexibility of elite-level coaches.